Collateral benefits: how the practical application of Good Participatory Practice can strengthen HIV research in sub‐Saharan Africa. (18th October 2018) - Baron, Deborah; Essien, Thandekile; Pato, Sinazo; Magongo, Miliswa; Mbandazayo, Nomthandazo; Scorgie, Fiona; Rees, Helen; Delany‐Moretlwe, Sinead
Abstract: Introduction: The Good Participatory Practice (GPP): Guidelines for Biomedical HIV Prevention Trials, second edition (2011) were developed to provide clinical trial sponsors and implementers with a formal stakeholder engagement framework. As one of the largest African research institutes, Wits Reproductive Health and HIV Institute (Wits RHI) became an early adopter of GPP by implementing its principles within large‐scale national and regional clinical trials. This article examines Wits RHI's lessons learned from implementing GPP, its ongoing efforts to institutionalize GPP, and the yet to be realized potential in creating fully sustainable structures for meaningful stakeholder engagement in HIV prevention research, implementation science and beyond. Discussion: For the past seven years, Wits RHI has undertaken both centralized leadership roles in implementing GPP across multi‐party regional research consortia as well as overseeing GPP for smaller investigator‐driven trials. Through this iterative roll‐out of GPP, key lessons have emerged. Obtaining upfront funding to support GPP activities throughout and between the research life cycle, and a trained multi‐disciplinary team of GPP practitioners have helped facilitate an enabling environment for GPP implementation. We further recommend formally integrating stakeholder engagement into study documents, including monitoring and evaluation plans with indicators and performance metrics, to assist teams to track and refine their GPP strategies. Finally, institutionalizing resources and supporting organization‐wide GPP along with ongoing support can help build efficiencies and maximize economies of scale toward a pragmatic and innovative application of the GPP Guidelines. Conclusions: Thanks to a growing global network of GPP practitioners and a burgeoning GPP Community of Practice, there has been substantive progress in making GPP an integral component of clinical HIV prevention research. The Wits RHI experience highlights the possibilities and the challenges to translating the GPP principles into concrete practices within specific clinical trials and across a research institute. Realizing the full potential of GPP, including direct and indirect – 'collateral benefits' will require the collective buy‐in and support from sponsors, implementers and community stakeholders across the research field. As the HIV prevention research field expands, however, a more conscious and systematic implementation of GPP is timely.